Teachers’ Beliefs on Parental Involvement in Children’s Transition from Home to ECE Settings - Fenmachi, Emela (International Journal of Educational and Life Transitions, 2024)
Children’s development is impacted by changes in the environments in which they interact. Normative transitions such as entry into an early childhood education (ECE) setting come with opportunities and challenges for children and their families. Supporting families and encouraging their involvement during the transition period enables children to understand their new environment and make new connections with teachers and classmates. This article analyses case studies from a doctoral research study based in Cameroon and identifies teachers’ beliefs on orientation processes and their contribution towards the transition process to ECE. Examples of transition practices in the study context are shared through data gained from semi-structured interviews, observations, and informal conversations, providing educators’ perspectives and the role of multiple caregivers in children’s daily activities. Findings reveal the need for building connections between teachers and families before families begin attending the educational context, as it allows the families’ individual needs to be better supported. The study provides evidence of the implications of orientation processes aimed at familiarising families and aiding their adaptation to a new educational context. The article considers teachers’ views on transition and suggests recommendations for effective orientation processes that address the specific needs of families.